How Public Health Professionals Perceive and Adapt to Emerging Health Threats - Darbani, Seyed Ali; Atapour, Neda (Journal of Foresight and Health Governance, 2024)
This study aims to explore how public health professionals perceive and adapt to emerging health threats. This study employed a qualitative research design using semi-structured interviews with 24 public health professionals recruited through online announcements and professional platforms. Data collection continued until theoretical saturation was achieved. The interviews were conducted virtually, transcribed verbatim, and analyzed using thematic analysis with NVivo software. Open coding, axial coding, and selective coding were applied to identify key themes related to professionals' perceptions, adaptive strategies, and barriers in responding to health threats. The results revealed three primary themes: perception of emerging health threats, adaptation strategies, and challenges in crisis response. Participants reported that their perception of threats was influenced by past experiences, institutional preparedness, and exposure to misinformation. Adaptation strategies included institutional policy adjustments, professional training, technological integration, and community engagement. However, participants also faced significant challenges, including policy and governance limitations, resource shortages, public resistance, and ethical dilemmas. The findings suggest that while public health professionals demonstrate strong adaptive capacities, systemic barriers continue to hinder their ability to implement effective responses. Understanding public health professionals' perceptions and adaptation mechanisms is crucial for improving crisis preparedness and response strategies. Strengthening institutional support, enhancing professional training, and addressing misinformation can contribute to more effective public health interventions. Future research should explore long-term workforce resilience and the role of emerging technologies in supporting adaptation.